2005
DOI: 10.1007/s00105-005-0910-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterung von Haaren und N�geln

Abstract: Human hair and nails, like all other organs, undergo chronological aging. Age-associated changes in growth, color, and structure of the hair and nails are common. In contrast to the aging process of the skin, the gerontobiological course of hair and nails has not been investigated comprehensively. Investigations on signaling pathways important for melanogenesis of the hair follicle improve our understanding of processes involved in hair greying. Differences in the structure and quality of the nails at an advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…Here, we showed that the expression of two members of the acidic keratin family, keratin KRT33A and keratin KRT34, decrease with age. As they represent the later differentiation of the hair follicle, we speculate that this might be aetiological for the previously reported changes in hair structure during ageing (11). Besides the hair keratins, KAPs represent the other main components of the hair fibre, forming the protein matrix between the keratin microfibrils (12) and playing a crucial role in forming a strong hair shaft (8).…”
Section: Resultssupporting
confidence: 52%
“…Here, we showed that the expression of two members of the acidic keratin family, keratin KRT33A and keratin KRT34, decrease with age. As they represent the later differentiation of the hair follicle, we speculate that this might be aetiological for the previously reported changes in hair structure during ageing (11). Besides the hair keratins, KAPs represent the other main components of the hair fibre, forming the protein matrix between the keratin microfibrils (12) and playing a crucial role in forming a strong hair shaft (8).…”
Section: Resultssupporting
confidence: 52%
“…Pathogenetisch wirkt eine Noxe auf den wachsenden Haarfollikel ein und bewirkt eine vorzeitige Beendigung der Anagenphase, welche frühzeitig in die Telogenphase übergeht [1,3]. Nach einer Latenz von drei bis vier Monaten setzt dann ein gesteigerter Haarausfall ein [3,15,20].…”
Section: Uses Telogenes E Uviumunclassified
“…[ 5 ] It is important to differentiate between chronological hair aging signs and pathological changes to offer our patients a prompt treatment. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%